2001
DOI: 10.1089/152460901300039467
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Health Interventions in Women: What Works?

Abstract: Women's Cardiovascular Health Network members representing 10 Prevention Research Centers completed a literature review of approximately 65 population-based studies focused on improving women's cardiovascular health through behavior change for tobacco use, physical inactivity, or diet. A framework was developed for conducting the search. Databases (Medline, Psychlit, Smoking and Health, Cumulative Index to Nursing and Allied Health Literature) of studies published from 1980 to 1998 were searched. The review wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 100 publications
(132 reference statements)
2
49
0
1
Order By: Relevance
“…Similar to other studies, this research found that participants discussed the importance of social support in supporting and maintaining healthy lifestyle behaviors (Eyler & Vest, 2002;Krummel, Koffman, Bronner, Davis, & Greenlund, 2001). This suggests the need to develop or enhance social support networks to improve women's health.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to other studies, this research found that participants discussed the importance of social support in supporting and maintaining healthy lifestyle behaviors (Eyler & Vest, 2002;Krummel, Koffman, Bronner, Davis, & Greenlund, 2001). This suggests the need to develop or enhance social support networks to improve women's health.…”
Section: Discussionsupporting
confidence: 83%
“…11,12 In the Nurses' Health Study, which monitored more than 80 000 women for 14 years, 82% of coronary events were attributed to lack of adherence to lifestyle guidelines involving diet, exercise, and smoking. 13 Furthermore, the most recent National Health and Nutrition Examination Survey, conducted between 1999 and 2000, found significant increases in the prevalence of obesity (30.1% with BMI Ն30 kg/m 2 ) and hypertension (34%) among women compared with prior surveys.…”
Section: Discussionmentioning
confidence: 99%
“…Although motivation has been identified as a primary determinant of health behavior change, interventions designed to enhance motivation in behavioral change have shown limited effectiveness (Krummel et al, 2001;Miller et al, 1997). Thus, there is a need to better understand how motivation contributes to the initiation and maintenance of behavioral change.…”
mentioning
confidence: 99%